2014
DOI: 10.1038/tpj.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Associations between functional polymorphisms in the NFκB signaling pathway and response to anti-TNF treatment in Danish patients with inflammatory bowel disease

Abstract: Antitumor necrosis factor-α (TNF-α) is used for treatment of severe cases of inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC). However, one-third of the patients do not respond to the treatment. Genetic markers may predict individual response to anti-TNF therapy. Using a candidate gene approach, 39 mainly functional single nucleotide polymorphisms (SNPs) in 26 genes regulating inflammation were assessed in 738 prior anti-TNF-naive Danish patients with IBD. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(168 citation statements)
references
References 53 publications
10
151
1
1
Order By: Relevance
“…Conversely, two common SNPs in the TLR9 gene (promoter flanking rs187084 and rs352140 in the second exon) which showed significance for both allele and genotype frequencies (p < 0.05) in our analysis (Table II) did not reach the level of significance in an earlier association study on the risk of invasive aspergillosis among recipients of allogeneic haematopoietic cell transplants [19]. Nevertheless, many other studies have proved associations of rs187084 and rs352140 with numerous immune-related diseases, response to therapies, as well as bacterial and viral infections in populations of both Western and Eastern Eurasian ancestry [20,21,22,23,24,25]. It is also worth noting that the common rs4586 SNP, flanking the promoter of CCL2 gene, which appeared significant for genotype frequencies between our cases and controls (p = 0.0079, OR = 8.5, Table II), was recently found to be significantly correlated with anti-tumour immune reaction in Korean patients with colorectal cancer [26] and associated with the clinical outcome in Japanese individuals with locoregional gastric cancer [27].…”
Section: Resultscontrasting
confidence: 71%
“…Conversely, two common SNPs in the TLR9 gene (promoter flanking rs187084 and rs352140 in the second exon) which showed significance for both allele and genotype frequencies (p < 0.05) in our analysis (Table II) did not reach the level of significance in an earlier association study on the risk of invasive aspergillosis among recipients of allogeneic haematopoietic cell transplants [19]. Nevertheless, many other studies have proved associations of rs187084 and rs352140 with numerous immune-related diseases, response to therapies, as well as bacterial and viral infections in populations of both Western and Eastern Eurasian ancestry [20,21,22,23,24,25]. It is also worth noting that the common rs4586 SNP, flanking the promoter of CCL2 gene, which appeared significant for genotype frequencies between our cases and controls (p = 0.0079, OR = 8.5, Table II), was recently found to be significantly correlated with anti-tumour immune reaction in Korean patients with colorectal cancer [26] and associated with the clinical outcome in Japanese individuals with locoregional gastric cancer [27].…”
Section: Resultscontrasting
confidence: 71%
“…Two SNPs in TLR2 (rs11938228 and rs4696480) with unknown function were associated with nonresponse, and this might indicate that TLR2 activity is associated with anti-TNF treatment, although the unknown function of the two SNPs makes the results difficult to interpret in a biological context. Similar associations for TLR2 (rs11938228, rs4696480) have been found when treating inflammatory bowel disease with anti-TNF, and for LY96 (rs11465996) when treating ulcerative colitis with anti-TNF, 6 supporting the notion of a possible association. Furthermore, a decrease in TLR2 levels has been found to be correlated with a decrease in PASI when treating psoriasis with anti-TNF agents 18 that could support the current findings.…”
Section: Study Populationsupporting
confidence: 66%
“…We selected genes involved in nuclear factor-κB, TNF-α and pattern recognition pathways as described by Bank et al 6 and Sode et al 8 Briefly, candidates were found by searching for 'polymorphism AND Gene name AND (reporter gene OR luciferase OR ELISA OR RT-PCR OR flow cytometry OR EMSA)' and the single-nucleotide polymorphism (SNP) candidates were chosen based on the reported functionality, association with autoimmune diseases or association with response. [6][7][8] A list of all SNPs studied is presented in Supplementary Table 1a.…”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations